A case-control study on egg consumption and risk of stroke among Iranian population - Roohallah Fallah-Moshkani; Mohammad Saadatnia; Forough Shakeri; Ammar Hassanzadeh Keshteli; Parvane Saneei; Bagher Larijani; Ahmad Esmaillzadeh (BMC, 2017)
Abstract Background Most available data that linked intake of egg to risk of stroke came from western countries, with conflicting findings. We aimed to examine the association between egg consumption and risk of stroke among Iranian adults. Methods In a hospital-based case-control study, 195 stroke patients, hospitalized in Alzahra University Hospital, were selected as cases and 195 control subjects, from patients hospitalized in other wards with no history of cerebrovascular diseases or neurologic disorders, were recruited. A validated 168-item food frequency questionnaire (FFQ) was used to assess participants' usual dietary intake, including egg consumption, over the previous year. Other required information was gathered by the use of questionnaires. Results Consumption of eggs was associated with lower odds of stroke, such that after adjustment for potential confounders, those in the highest category of egg intake (>2 eggs/week) were 77% lower odds to have stroke, compared with those with the lowest category of egg intake (<1 egg/week) (OR 0.23; 95% CI 0.11-0.45). Further controlling for body mass index strengthened the association (OR 0.20; 95% CI 0.09-0.41). Conclusions We found evidence indicating that high intake of eggs (>2 eggs/week) during the past 1 year was associated with a lower risk of stroke. Further prospective studies are required to confirm these findings.